Corporate governance, transparency and performance: empirical evidence from UAE. (13th July 2022) - Hassan, Mostafa Kamal; Florio, Cristina; Abbas, Bassam Abu
The paper uses both the agency theory and the legitimacy theory to provide a complementary framework that links different patterns of disclosures (i.e., transparency) to corporate performance for a sample of 116 United Arab Emirates (UAE) listed firms between years 2008-2016. It investigates the relationship between corporate disclosures (i.e., transparency), organisational commitment to law, a set of governance mechanisms (namely, board size, CEO decision-making power, and foreign ownership) and corporate performance while controlling for corporate specific characteristics such as size, type, age and leverage. The empirical results show that transparency indices have a puzzling pattern across different performance measures - namely return on assets, asset turnover and organisational growth. The paper is one of very few studies that examine the association between corporate transparency and corporate performance in an emerging market economy such as the UAE.